Water outage increases the risk of gastroenteritis and eyes and skin diseases - Chou Chang-Hung; Wu Trong-Neng; Liu Chung-Ming; Wang Yu-Chun; Huang Ling-Ya; Sung Fung-Chang; Wu Chin-Ching (BMC, 2011)
Abstract Background The present study used insurance claims data to investigate infections associated with short-term water outage because of constructions or pipe breaks. Methods The present study used medical claims of one million insured persons for 2004-2006. We estimated incidences of gastroenteritis and eye and skin complaints for 10 days before, during, and after 10 days of water supply restriction for outpatient visits and for emergency and in-patient care combined. Results There was an increase in medical services for these complaints in outpatient visits because of water outages. Poisson regression analyses showed that increased risks of medical services were significant for gastroenteritis (relative risk [RR] 1.31, 95% confidence interval [CI] 1.26-1.37), skin disease (RR 1.36, 95% CI 1.30-1.42), and eye disease patients (RR 1.34, 95% CI 1.26-1.44). Similar risks were observed during 10-day lag periods. Compared with those in cool days, risks of medical services are higher when average daily temperature is above 30°C for gastroenteritis (RR 12.1, 95% CI 6.17-23.7), skin diseases (RR 4.48, 95% CI 2.29-8.78), and eye diseases (RR 40.3, 95% CI 7.23-224). Conclusion We suggest promoting personal hygiene education during water supply shortages, particularly during the warm months.